2014
DOI: 10.1039/c3ra47911k
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-catalyzed Suzuki reaction in aqueous solvents applied to unprotected nucleosides and nucleotides

Abstract: Nucleoside analogues have attracted much attention due to their potential biological activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(30 citation statements)
references
References 86 publications
1
29
0
Order By: Relevance
“…The presence of the chlorine or of the oxygen atoms did not seem to change the lipophilic properties of the reactant. Consequently compounds 45, 46 and 47 were isolated in the same range of yields (Table 4, entries [6][7][8]. In order to modulate the structure, substitution (M = Na + , K + ) (10 to 20 mol%) in presence of CuI (0.2 eq to 0.5 eq) and NEt 3 (2 eq to 10 eq).…”
Section: Pd(ii)-catalyzed Heck Cross-coupling In H 2 Omentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the chlorine or of the oxygen atoms did not seem to change the lipophilic properties of the reactant. Consequently compounds 45, 46 and 47 were isolated in the same range of yields (Table 4, entries [6][7][8]. In order to modulate the structure, substitution (M = Na + , K + ) (10 to 20 mol%) in presence of CuI (0.2 eq to 0.5 eq) and NEt 3 (2 eq to 10 eq).…”
Section: Pd(ii)-catalyzed Heck Cross-coupling In H 2 Omentioning
confidence: 99%
“…In order to use safer solvents and auxiliaries, to limit the risks and hazards, different groups have reported recently those cross-couplings in greener solvents such as water without the need for protection and deprotection steps. Since recent developments and a complete review on Suzuki-Miyaura reaction applied to unprotected nucleosides were reported by our group [7,[12][13][14][15], this paper will focused on the Heck reactions and Sonogashira reactions applied to unprotected nucleosides and nucleotides in aqueous media or water as sole solvent. For the sake of clarity, this review has been arranged to describe the Heck reaction and then the Sonogashira reaction.…”
mentioning
confidence: 99%
“…Compared to related C-C bond formations, the environmentally benign nature, high functional group tolerance, wide commercial availability of the reactants, and compatibility with aqueous conditions are advantageous [10][11][12]. As a result, various research groups have utilized and reviewed this reaction for the derivatization of complex molecules such as natural products [13][14][15][16] and nucleosides [17][18][19][20][21][22][23]. The mechanism of this reaction originally proposed by Miyaura and Suzuki has been revisited recently, which provides insights useful for rational reaction optimization [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…In the context of green chemistry, catalysis and alternative media, different cross-coupling reactions such as Suzuki-Miyaura in batch reactors have been developed in aqueous media or in water as sole green safer solvent via conventional heating or microwave irradiation [32][33][34][35][36][37][38][39][40][41][42][43]. Continuous flow chemistry as alternative technology offers significant processing advantages including improved thermal management, mixing control, application to a wider range of reaction conditions, scalability, energy efficiency, waste reduction, safety, use of heterogeneous catalysis, multistep synthesis and much more [44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%